[PP.35.03] ALDOSTERONE, RENIN AND THE ALDOSTERONE-TO-RENIN-RATIO: AGE- AND SEX-SPECIFIC DISTRIBUTION AND DETERMINATS IN THE POPULATION. (September 2016) - Hermanns, M.I.; Matheis, S.; Arnold, N.; Prochaska, J.H.; Panova-Noeva, M.; Schulz, A.; Laubert-Reh, D.; Lackner, K.J.; Münzel, T.; Wild, P.S.
Abstract : Objective: Renin-angiotensin-aldosterone system (RAAS) plays a key role in the regulation of human blood pressure. Recent investigations have demonstrated that both a higher aldosterone concentration and a higher aldosterone-to-renin-ratio serve as markers of increased risk for hypertension. However, the distribution of the aldosterone-to-renin-ratio in the general population is largely unknown. We aimed to provide a sex-specific distribution and reference ranges for plasma aldosterone concentration (PAC), plasma renin concentration (PRC) and its ratio in a large population-based sample. Design and method: PAC and PRC were analyzed by chemiluminescent immunoassay (CLIA) (LIAISON®, DiaSorin) in a sample of 7, 474 (50.7%) men and 7, 266 (49.3%) women from the population-based Gutenberg Health Study in Germany. Multivariable regression analyses for PAC, PRC and the aldosterone-to-direct-renin-ratio (ADRR) were performed under adjustment for age, medication, cardiovascular risk factors (CVRFs) and cardiovascular disease (CVD). Biomarkers and the ratio were log-transformed. Reference subgroups were selected by excluding hypokalemia, CVRFs, CVD, renal insufficiency, and intake of analyte modifying drugs. The reference interval was defined as the central 95% range between the 2.5th and 97.5th percentiles. Results: Results showed sex differences in PAC, PRC and ADRR with lower PRC and higher PAC and ADRR in females than in males. PRC decreased with age in males and females whereas PAC decreased was significant in females only. The ADRR increased with age (ßlog (ADRR) per 5y: 0.08 [95%CI: 0.06/0.09]) and 0.06 [0.05/0.08] for men and women, resp.; p < 0.0001). Thus, age- and sex-specific nomograms for PAC, PRC, and ADRR were created by quantile regression. In multivariable analysis, PAC was positively associated with obesity and dyslipidemia. Both, PAC and PRC were elevated for chronic kidney disease, while the ADRR showed no association. In a fully adjusted multivariable model, the strongest correlation observed was found for hypertension with elevated ADRR in both sexes. Conclusions: Based on a large population-based data set, the present investigation provides a comprehensive characterization of the distribution and reference ranges for PAC, PRC and the ADRR in a predominantly Caucasian sample. Age- and sex-related limits of PAC, PRC, and the ADRR could support clinicians in diagnosis and treatment of hypertension.